Dorstenia arachniformis (Moraceae), a new species from Combretum wooded grasslands in Makueni County, Kenya - Malombe, Itambo; Matheka, Kennedy Wambua; Mwadime, Thomas; Mwachala, Geoffrey (Phytotaxa, 2020)
A new species of Dorstenia (Moraceae), D. arachniformis, is described from the Combretum wooded grassland vegetation relicts in south-eastern Kenya. The species is distinguished from the closely related D. goetzei by features of the receptacle and appendages. An assessment of the conservation status of the new species is provided.